Changes of Trigeminal Ganglion Neurons Innervating the Temporomandibular Joint in Chronic Pain Rat Model - Wen Liu; Henghua Jiang; Jin Ke; Xin Liu; Yaping Feng; Jinsong Hou; Xing Long (International Journal of Dentistry)
Conclusion: This study suggests that sensitization of small- to medium-sized Dil+ TG neurons and CGRP- and IB4-positive Dil+ TG neurons might contribute to the development of TMJOA chronic pain in rats. This will provide valuable information for more efficient control of TMJOA chronic pain.